Islam is Not Only a Religion but a Complete Way of Life - Mudathir, Bawa Sani (International Journal of Research in Interdisciplinary Studies, 2025)
This study examines Islam as a comprehensive way of life, analyzing its holistic nature that encompasses spiritual, social, economic, political, and personal dimensions of human existence. Through an integrated textual and contextual analysis approach, this research investigates how Islamic principles provide guidance for all aspects of human affairs from individual conduct to societal governance. The study employed a mixed-methods design incorporating qualitative data from 45 in-depth interviews with Islamic scholars, imams, community leaders, and practitioners, alongside quantitative survey data from 420 respondents across different Muslim communities. Findings reveal the comprehensive nature of Islamic teachings, with 82% of respondents affirming Islam's role as a complete way of life while 79% acknowledging the necessity of implementing Islamic principles in all spheres of human activity. The research contributes to understanding how Islamic communities maintain the holistic application of Islamic teachings while engaging with contemporary global challenges. Results indicate that Islamic life experience reflects broader patterns of religious authenticity and adaptation in modern societies, offering insights into Islamic governance systems, community-based ethics, divine knowledge frameworks, and intergenerational transmission of Islamic practices in rapidly changing contexts.